2009
DOI: 10.1159/000210656
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production Profile of CD4+ T Cells from Patients with Active Churg-Strauss Syndrome Tends Toward Th17

Abstract: Background: Churg-Strauss syndrome (CSS) is a rare systemic necrotizing vasculitis that develops in some asthma patients. What types of asthma make patients prone to develop this condition remains unknown. We found that inhibition of regulatory T cells (Treg) differentiation, especially by Tr1 cells, due to a decreased ability of responder T cells to generate IL-2, is associated with the onset and pathogenesis of CSS. In contrast, recent evidence suggests that IL-17-producing Th17 cells play a crucial role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…Accordingly, the proportion of IL-10-producing T cells in SA-2-treated mice was inhibited by the anti-IFN-aR-and, poorly, anti-IL-10R Abs. These data are consistent with the increased IFN-a in the serum and elevated IL-10-producing T cells during the remission of respiratory symptoms in severe asthma and ChurgStrauss syndrome (41). Thus, it is reasonable to hypothesize that IL-10 and IL-10-inducing cytokines are the major players for the early and delayed inhibition of NKT cell-derived cytokines, including IL-17A.…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly, the proportion of IL-10-producing T cells in SA-2-treated mice was inhibited by the anti-IFN-aR-and, poorly, anti-IL-10R Abs. These data are consistent with the increased IFN-a in the serum and elevated IL-10-producing T cells during the remission of respiratory symptoms in severe asthma and ChurgStrauss syndrome (41). Thus, it is reasonable to hypothesize that IL-10 and IL-10-inducing cytokines are the major players for the early and delayed inhibition of NKT cell-derived cytokines, including IL-17A.…”
Section: Discussionsupporting
confidence: 79%
“…The Th17 subset also appears to subvert Tregdriven immunosuppression; unlike IFN-␥, Th17-associated IL-6 inhibits rather than enhances tryptophan catabolism, which is a process associated with Treg induction (18). In the absence of attenuation, Th17-associated effector mechanisms can mediate tissue injury through protracted local inflammation, a feature of certain chronic biofilm infections (20,29,78,84).…”
Section: Protective Mechanisms Of the Il-17 Axismentioning
confidence: 99%
“…We confirmed that the percentage of CD4+ T cells producing IL-17 was significantly greater in patients with active CSS than in healthy control patients or in patients with asthma, BA + CEP, or inactive CSS ( producing IL-17 in active CSS who were at onset or at relapse was significantly greater than those in inactive CSS and the percentage of CD4+CD25+ T cells producing IL-10 (Tr1 cells) in active CSS significantly decreased than those in inactive CSS who achieved remission after treatment (Tr 1) ( Fig. 9) (Saito et al, 2009). Th17 cells were identified as CD4+ T cells that produced mainly IL-17 and IL-22.…”
Section: Specificitymentioning
confidence: 92%